Double extraction of olive oil in large oil mills of Southern Italy: Effects on extraction efficiency, oil quality, and economy of the process. Issue 1 (21st November 2016) - Di Giovacchino, Luciano; Preziuso, Serena Maria; Di Serio, Maria Gabriella; Mucciarella, Maria Regina; Di Loreto, Giuseppina; Lanza, Barbara
Abstract : In recent years, in Italy, some large oil mills, equipped with centrifugal decanter at high loading capacity have adopted the complex diagram of the double extraction of oil and, in addition, have been supplied with suitable machine to recover part of stone fragments from olive pomace with the aim to reduce the costs. Our experimental tests were carried out in a large oil mill, located in Apulia region, which processes olives of Olea europaea L. "Coratina" cultivar by double centrifugation of olive pastes prepared by using the double crushing (millstones and metallic crusher) or the single crushing (metallic crusher). The results showed that the oil yield of the first extraction was high (between 85 and 86%), regardless to the method used for olive crushing. The quality of virgin olive oil of the first extraction was extra virgin with some differences due to the different batches of olives and, in part, also to the used crushing methods. The oil of the second extraction was recovered in a low quantity (0.3 kg/100 kg olives) and its composition was not normal only for the percentage of triterpene dialcohols. The recovery of stone fragments was satisfying (about 0.13 t/t olives) and helped to significantly increase the income of oil mill. Practical applications : The double extraction of oil, by the centrifugation system, and the recovery of SF allow to reduce the costs of olive processing in medium‐big sized oil mills. The second centrifugation, which permits to recover about 3 kg of oil/t of olives, and the recovery of SF, suitable to sell as fuel, allow to increase the income of oil mill. The double extraction of oil, by the centrifugation system and the recovery of olive stone fragments (SF) allow to reduce the costs of olive processing in medium‐big sized oil mills. The second centrifugation, which permits to recover about 3 kg of oil/t of olives, and the recovery of SF, suitable to sell as fuel, allow to increase the income of oil mill. Abstract : The double extraction of oil, by the centrifugation system and the recovery of olive stone fragments (SF) allow to reduce the costs of olive processing in medium‐big sized oil mills. The second centrifugation, which permits to recover about 3 kg of oil/t of olives, and the recovery of SF, suitable to sell as fuel, allow to increase the income of oil mill.